The Application of the Loud Reading Strategy (Al Qira’ah Al Jahriyyah) Based on Pop-Up Books in Enhancing Arabic Reading Skills - Fitriyani, Nur; Supriadi, Rinaldi; Agustika Putri, Kristie; Nurbayan, Yayan; Kasver Mathiessen, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study employs an action research method to evaluate the effectiveness of a read-aloud strategy using pop-up books in improving Arabic reading skills among 20 students of Class VI B at Nurul Amal Elementary School, Bandung. The research, conducted over two cycles, addresses challenges such as difficulty understanding Arabic texts and a lack of engaging learning media, which led to low reading interest and skills. In the pre-cycle phase, students achieved an average score of 40.5, with only 10% learning success. This improved in Cycle I, with an average score of 74.5 (45% success), and further in Cycle II, with an average score of 89.25 (85% success). A Likert-scale questionnaire also showed an 87.8% positive response. The findings conclude that the read-aloud strategy with pop-up books effectively enhances students' Arabic reading skills and engagement